A holocentric twist to chromosomal speciation?. (August 2022) - Lucek, Kay; Augustijnen, Hannah; Escudero, Marcial
Abstract : Chromosomal rearrangements trigger speciation by acting as barriers to gene flow. However, the underlying theory was developed with monocentric chromosomes in mind. Holocentric chromosomes, lacking a centromeric region, have repeatedly evolved and account for a significant fraction of extant biodiversity. Because chromosomal rearrangements may be more likely retained in holocentric species, holocentricity could provide a twist to chromosomal speciation. Here, we discuss how the abundance of chromosome-scale genomes, combined with novel analytical tools, offer the opportunity to assess the impacts of chromosomal rearrangements on rates of speciation by outlining a phylogenetic framework that aligns with the two major lines of chromosomal speciation theory. We further highlight how holocentric species could help to test for causal roles of chromosomal rearrangements in speciation. Highlights: Chromosomal speciation, whereby major chromosomal rearrangements trigger reproductive isolation, is a classic evolutionary concept. The underlying theory was developed for chromosomes with centromeres when holocentric chromosomes that lack centromeres have repeatedly evolved across the tree of life. We argue that holocentricity may help to overcome problems associated with classic chromosomal speciation theory and that the special characteristics of holocentric chromosomes vastly expand the potential for experimental research on chromosomal speciation. We outline how new approaches allow quantification of the macroevolutionary impact of chromosomal speciation and the ability to distinguish the associated evolutionary mechanisms.